Analysis and Implementation of Metode Collaborative Analysis Methods of Requirement and Design (CARD) on E-commerce Website in Indonesia - Oktariantoro Anggit K; Angelina Prima K; Erda Guslinar P (International Journal on Information and Communication Technology (IJoICT), 2015)
The development of internet in recent years caused a major prospect in online business. One of the businesses is e-commerce. E-commerce is an activity of selling and buying information through computer network. Website is a medium that can be used in e-commerce implementation. E-commerce website becomes an important part in supporting the companys success. Yet, there are many e-commerce websites that are not understandable by the user since the user cannot find out what they want. In addition, e-commerce website is still difficult to use. The users who cannot find what they want in e-commerce website will surely decrease the usability of the website. As a result, there must be a design planning which can be comprehended by the users to find the expected product easily. The Collaborative Analysis of Requirement and Design method can be used to solve the design problem. The method is one of the techniques in user centered design. The method focuses on users because in its process it involves the users, and the users are the the information source of this method. The information that is gained from the users can be taken form interview, questionairre and experimentation with component order. The result of this research gives contribution to the websites, that is advise to improve the website design so that the users can understand the working system and the design more comprehensively.